Edukasi Dengan Media Booklet Terhadap Pengetahuan Gizi Prakonsepsi, Sikap dan Asupan Zat Gizi Makro Wanita Pranikah - Putri, Pratiwi Hariyani; Nur Ainani, Farah Nilna; Yuliani, Kartika; Sunaryo, Merry; Puspitasari, Putri (citeus, 2021)
The prevalence of chronic energy deficiency(KEK) in Jombang District has a percentage of 15.17% in women who are not pregnant and 12.63% in women of childbearing agewho are pregnant (Kemenkes RI, 2018). The high prevalence of chronic energy deficiency (KEK)in women of childbearing agein JombangDistrict, which exceeds the average in East Java, indicates that there are problems that need special attention. This study aims to analyze the effect of nutrition education with booklet media on preconception nutrition knowledge, attitudes and macronutrient intake of premarital women. This type of research is a quasi-experimental. The design used pre-post test control group design. The results of the study indicate that there is an effect of education with booklet media on nutritional knowledge of premarital women (p = 0,008), there is an effect of education with booklet media on the attitude of premarital women (p = 0,001), there is an effect of education with booklet media on energy intake (p = 0,020), protein (p = 0,025), lemak (p = 0,005), karbohidrat (p = 0,034). Education using booklet media affects preconception nutrition knowledge, attitudes and macronutrient intake. This happens because the booklet media is easy to understand, can be taken anywhere and can be read at any time so that this media isvery effective.